Alternative neural circuitry that might be impaired in the development of Alzheimer disease - Avila, Jesus; Perry, George; Strange, Bryan A.; Hernandez, Felix (Frontiers in Neuroscience, 2015)
It is well established that some individuals with normal cognitive capacity have abundant senile plaques in their brains. It has been proposed that those individuals are resilient or have compensation factors to prevent cognitive decline. In this comment, we explore an alternative mechanism through which cognitive capacity is maintained. This mechanism could involve the impairment of alternative neural circuitry. Also, the proportion of molecules such as Aβ or tau protein present in different areas of the brain could be important.